The Carotenoid Composition of Larvae Feed Is Reflected in Adult House Fly (Musca domestica) Body - Li-Or Lahmi; Ayelet Harari; Aviv Shaish; Ido Tsurim (Insects, 2024)
Carotenoids are common and diverse organic compounds with various functional roles in animals. Except for certain aphids, mites, and gall midges, all animals only acquire necessary carotenoids through their diet. The house fly (Musca domestica) is a cosmopolitan pest insect that populates diverse habitats. Its larvae feed on organic substrates that may vary in carotenoid composition according to their specific content. We hypothesized that the carotenoid composition in the adult house fly’s body would reflect the carotenoid composition in the larval feed. House fly larvae were reared on diets that differed in carotenoid composition. HPLC analysis of the emerging adult flies indicate that the carotenoid composition of adult house flies is related, but not identical, to the carotenoid composition in its natal substrate. These findings may be developed to help identify potential sources of house fly infestations. Also, it is recommended that rearing substrates of house fly larvae, used for animal feed, should be carefully considered.